(2S, 4R)-Hyp-(S)-Phe-OMe dipeptide supported on imidazolium tagged molecules as recoverable organocatalysts for asymmetric aldol reactions using water as reaction medium. Issue 36 (7th September 2017) - Obregón-Zúñiga, Arturo; Juaristi, Eusebio
Abstract: Four novel chiral imidazolium tagged molecules derived from dipeptide (2 S, 4 R )-Hyp-( S )-Phe-OMe were prepared and evaluated as organocatalysts in the asymmetric aldol reaction using water as solvent. It was found that catalysts incorporating the hexanoyl linker are active down to 5 mol% and afford aldol products with up to 94% yield, up to 98:2 dr and up to 97:3 er. This chiral imidazolium catalyst was reused up to 6 times without any loss in the stereoselectivity of asymmetric aldol reactions. By contrast, organocatalysts containing an acetyl linker proved to be highly unstable in protic solvents, and for that reason they could not be recovered and reused. Graphical abstract: